Giải bất pt (2x-4)(x+3)-3x+1 ≤(x-1)(x+2)+x^2-7

Question

Giải bất pt
(2x-4)(x+3)-3x+1 ≤(x-1)(x+2)+x^2-7

in progress 0
Natalia 2 tháng 2021-07-25T21:24:19+00:00 2 Answers 1 views 0

Answers ( )

    0
    2021-07-25T21:25:55+00:00

    Đáp án:

     

    Giải thích các bước giải:

    \(\begin{array}{l}
    2{x^2} + 2x – 12 – 3x + 1 \le {x^2} + x – 2 + {x^2} – 7\\
     \Leftrightarrow {x^2} – 2x – 2 \le 0\\
     \Leftrightarrow (x – 1 – \sqrt 3 )(x – 1 + \sqrt 3 ) \le 0\\
     \to x \in \left[ {1 – \sqrt 3 ;1 + \sqrt 3 } \right]
    \end{array}\)

    0
    2021-07-25T21:25:58+00:00

    Đáp án:

     

    Giải thích các bước giải:

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )